A Comparison Between Catalase and Salivary Alpha Amylase Level in Patients with Diabetic and Non Diabetic (Medical Forum Monthly, 2023)
Objective: To compare the salivary catalase and alpha amylase level in patients with diabetes and non-diabetes.Study Design: Analytical descriptive studyPlace and Duration of Study: This study was conducted at the Physiology department of Bakhtawar Amin Medical & Dental College, Multan from February 2022 to January 2023.Materials and Methods: A total of 112 patients were enrolled in study. Saliva of 56 diabetic individuals 56 non diabetic individuals was gathered and sent to laboratory. Level of salivary alpha amylase and catalase was determined separately. Level of enzymes was compared between diabetic and non-diabetic groups. Mean (standard deviation and frequency (percentages) were calculated by using SPSS version 23 for data analysis.Results: The mean salivary catalase enzyme in diabetes and non-diabetes patients was 497.21±52.81 KU/I and 292.52±39.08 KU/I, respectively. In diabetes patients, the average level of salivary catalase enzyme was greater than the non-diabetes patients. This difference was statistically significant, (p<0.000). The mean alpha-amylase level in diabetes and non-diabetes patients was 160060.71±166.15IU/ml and 82922.75±175.36IU/ml, respectively. In diabetes patients, the average alpha-amylase level was greater than the non-diabetes patients.Conclusion: In diabetes type 1 patient’s level of salivary alpha amylase and catalase is higher in diabetic patients as compared to diabetic healthy subjects.